Three new species of free-living marine nematodes from East China Sea - Chen, Yuzhen; Guo, Yuqing (Zootaxa, 2014)
Three new species of free-living marine nematodes from intertidal sands in Xiamen, Fujian province are described and illustrated. Bathylaimus denticulatus sp. n. can be distinguished by a relatively small buccal cavity with its second part armed with two distinct teeth, short 2–3 μm labial and 12–16 μm cephalic setae and amphids of 0.8–0.9 turns. Oncholaimus minor sp. n. is characterized by its relatively small body size and the sexual dimorphism in tail shape. Oncholaimus xiamenense sp. n. is identified by pronounced sexual dimorphism in tail shape, the location of postcloacal tubercle (3/4 of the distance from cloaca to tip of tail), the location of female ovary as well as the demanian system (on the right side of the intestine), the number of circumanal genital setae (12). The types are deposited in the Third Institute of Oceanography, SOA, Xiamen.